SIMULACRA IN SUSTAINABILITY ACCOUNTING: A DECONSTRUCTIVE OF CORPORATE ENVIRONMENTAL REPORTS AS HYPERREALITY - Pujangga Abdillah; Lilik Purwanti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study investigates how accounting and financial reporting practices are utilized by companies as instruments to build a positive corporate image and secure legitimacy from stakeholders. The research uses a content analysis of the retirement reports of six mining and energy companies in Indonesia. The interpretation of these findings is based on Jean Baudrillard's theory of simulacra. The results reveal that while 96.8 percent of positive sustainability issues were reported, only 30.5 percent of negative issues appeared in the coverage, indicating significant continuity in the presentation of information. From a Baudrillardian perspective, the retirement reports produced by these companies embody four levels of simulacra, suggesting that management accounting plays a central role in shaping these simulacratic representations. Sustainability report deconstruction must be designed and directed to realize sustainable business or sustainable corporation. Narratives related to negative news, not just positive news that should be disclosed.